STUDY ETNOMATEMATIKA PADA AKTIVITAS PENGRAJIN ANYAMAN BAMBU MASYARAKAT SEJANGKUKNG - Ghita Ayu; Agung Hartoyo; Asep Nursangaji (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study aimed to describe the mathematical concepts found in the activities of bamboo weaving craftsmen in the form of nyiru, capil and bakul of the Sejangkung community. The subjects in this study were the Sejangkung community consisting of four people who were selected based on their ability to make woven crafts from bamboo. The form of research used was exploratory research with an ethnographic approach. The results and data analysis obtained from this study were (1) In the craftsmen's activity in choosing bamboo that is suitable for use, determine the thickness of the ilik, determine the woven motif, and determining the length, width, and height of the plait containing the set concept, logical concepts, proportion concepts, ratio concepts, geometry concepts, number pattern concepts, geometric transformation concepts, and the concept of multiplication operations on integers. (2) In the craftsmen's activities in cleaning and determining the length of bamboo, ilik drying process, and determine the pituk on the webbing contained the concept of measurement. (3) The activity of craftsmen in making woven patterns contained the concept of folding symmetry. (4) The activity of the craftsman determined the location of the motif in one woven which contains the concept of distance. Keywords: Study Ethnomathematics, The Sejangkung Community, Weaving Craftsman Activity